A Critique of the Supreme Court of Sierra Leone’s Conviction of Augustine Marrah for Criminal Contempt - Marrah, Augustine Sorie-Sengbe (Strathmore Law Journal, 2021)
The Legal Practitioners Act of 2000 authorises the Sierra Leone Bar Association to elect six legal practitioners for membership of the General Legal Council (Council), which is the regulatory body of the legal profession in Sierra Leone. In April 2019, Ibrahim Sorie was among the legal practitioners elected to the Council. Subsequently, I—another legal practitioner—objected to and petitioned in the High Court of Sierra Leone Sorie’s election to the Council on the basis of ineligibility. The thrust of my objection was that Sorie, a two-term ex-president of the Sierra Leone Bar Association had not yet attained the necessary fifteen-year standing qualification at the date of his appointment to the Council, based on his year of enrolment into the Permanent Register or Roll of Court in 2011. Sorie filed an action in the Supreme Court against the Council invoking the exclusive original jurisdiction of the Supreme Court to interpret certain portions of the Constitution of Sierra Leone vis-à-vis the eligibility provision for membership to the Council in the Legal Practitioners Act.2 The Supreme Court delivered a controversial 97-paged judgment on 27 October 2020.